Correlates of resilience after childhood sexual abuse among men who have sex with men. Issue 3 (26th May 2020) - Dale, Sannisha K.; Sanders, Jasmyn; Safren, Steven A.; Ironson, Gail; O'Cleirigh, Conall
ABSTRACT: Men who have sex with men (MSM) are at high risk for physical and mental health conditions and are often discussed in the health literature as "at risk" versus "at promise". However, there is an ongoing need to examine factors that place MSM "at promise" for optimal well-being. This manuscript examines correlates of resilience, the ability to "bounce back" and function adaptively after adversities, among MSM. One hundred and five MSM with a history of childhood sexual abuse, who were enrolled in a randomized control trial were recruited for a supplemental study assessing resilience and other psychosocial factors. Participants completed measures assessing resilient trait and coping (i.e. "I am able to adapt" and "I tend to bounce back"), symptoms of trauma, trauma-related thoughts, and distress tolerance (ability to regulate unpleasant feelings). Findings from multivariable linear regressions controlling for covariates (age, education, race/ethnicity, and income) indicated that higher resilience was associated with (a) lower trauma scores on reexperiencing severity ( b = −1.41, SE = .53, p = .01) and avoidance severity ( b = −1.61, SE = .67, p = .02), (b) lower post-traumatic cognitions ( b = −11.39, SE = 5.08, p = .03) especially negative cognitions about the self ( b = −.44, SE = .16, p = .007), and (c) higher distress tolerance ( b = .26, SE = .10, p = .01). Our preliminary findings suggest that resilient coping/traits are important to research after childhood sexual abuse among MSM, potentially assess in clinical settings, and address in interventions.